2022
DOI: 10.3390/ijerph19053139
|View full text |Cite
|
Sign up to set email alerts
|

Central Persons in Sustainable (Food) Consumption

Abstract: What people eat has become a highly political issue, closely intertwined with public health, environmental concerns, and climate change. Individuals’ consumption decisions tend to be greatly influenced by the people that surround them, and this seems to be especially true when it comes to food. In recent years, alongside close contacts, such as family and friends, a myriad of social influencers have appeared on the screens, sharing opinions on what (not) to eat. Presenting results from a youth survey conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 68 publications
(92 reference statements)
0
15
0
Order By: Relevance
“…These were the only statistically significant variations found in the study. On the contrary, a Swedish study (Zorell, 2022) of young people (ages 16 to 24) on how consumption decisions tend to be greatly influenced by the people that surround them, found that ecological criteria rank lowest in influence on food choice among youth. However, there were notable differences between men and women.…”
Section: Consumer Expectations Of Food Origin and Traceabilitymentioning
confidence: 95%
See 2 more Smart Citations
“…These were the only statistically significant variations found in the study. On the contrary, a Swedish study (Zorell, 2022) of young people (ages 16 to 24) on how consumption decisions tend to be greatly influenced by the people that surround them, found that ecological criteria rank lowest in influence on food choice among youth. However, there were notable differences between men and women.…”
Section: Consumer Expectations Of Food Origin and Traceabilitymentioning
confidence: 95%
“…• Family and friends (Zorell, 2022;Kılıç et al, 2020) • School (Zorell, 2022) EFSA Supporting publication 2023:EN-8203…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study is concerned with large production and consumption of hazardous and wasteful food which cause growing environment and health problems. These problems were behind the risk of increasing in preventable diseases, early deaths, and environmental disasters through the entire world [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social scientists, social psychologists, and behavioural economists show in numerous studies that social norms, social facilitation, shared social identities (e.g., social class, culture, gender, age, etc. ), or being a social role model or 'central person' can be key factors affecting whether, what, when, and how much individuals eat (3)(4)(5)(6)(7)(8)(9). Likewise, studies from media, education, and health research show that exposure to more as well as to less obvious forms of advertisements, marketing, and recommendations, especially in social media, can affect individual attitudes towards certain food products and the likelihood to consume them -even when individuals disapprove or are unwilling to acknowledge such in uence (10,11).…”
Section: Introductionmentioning
confidence: 99%